Economic Gender gap in the Global South: How Public Institutions Matter. - Bárcena-Martín, Elena María; Medina-Claros, Samuel; Pérez-Moreno, Salvador Jesús (Springer Nature, 2021)
One of the most challenging gender gaps in the Global South remains in the economic sphere. This paper examines how public institutions affect the gender gap in economic participation and opportunities in 74 developing and emerging countries during the period 2006-2016. We find that the public institutional environment is closely related to the economic gender gap. Specifically, the protection of property rights and guaranteeing security seem to be two key factors associated to lower economic gender inequality. Nevertheless, public institutions do not matter equally throughout economically backward countries. Whereas in emerging countries, particularly in Latin America and the Caribbean, a broad variety of institutional aspects, including undue influence on judicial and government decisions, are closely related to the economic gender gap, in low-income developing countries, such as Sub-Saharan countries, the problems of ethics and corruption stand out as a particularly remarkable element against economic gender equality. Some significant policy implications are derived from our findings regarding the potential of public institution reforms to reduce the economic gender gap.
Polkítica de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/16633
Keywords: Sexismo - Aspectos económicos; Países en desarrollo; Desarrollo económico y social; Administración pública; Economic gender gap; Economic participation and opportunities; Public institutions; Developing and emerging countries